Effect of central corneal thickness on intraocular pressure and comparison of Topcon CT-80 non-contact tonometry with Goldmann applanation tonometry - Mansoori, Tarannum; Balakrishna, Nagalla (Clinical and experimental optometry, 2018)
To compare intraocular pressure (IOP) measurements obtained with the Topcon CT-80 non-contact tonometer (NCT) and Goldmann applanation tonometer (GAT), in different ranges of IOP in normal and glaucoma subjects, and to assess the influence of central corneal thickness (CCT) on the IOP measurements in Asian Indian eyes. Four hundred and two eyes of 402 subjects (193 newly diagnosed primary open angle glaucoma [POAG] and 209 normal) were enrolled for this prospective study. For each eye, IOP was measured with GAT by a glaucoma specialist and NCT by a trained optometrist. The IOP values were compared among the tonometers in the three different IOP ranges (≤ 12 mmHg, 13-20 mmHg and ≥ 21 mmHg) using Bland-Altman graphs. Correlation between GAT and NCT was assessed by Pearson correlation co-efficient. CCT was measured with ultrasound pachymetry and its correlation with GAT and NCT was analysed using linear regression analysis. The mean paired difference of IOP between NCT and GAT was 1.556 ± 2.69 mmHg (r = 0.26, p = 0.006) at IOP range of ≤ 12 mmHg, −1.665 ± 2.6 mmHg (r = 0.51, p < 0.0001) in IOP range of 13-20 mmHg and −2.202 ± 3.44 mmHg (r = 0.82, p < 0.0001) in the IOP range of ≥ 21 mmHg. Linear regression analysis showed a mean IOP variation of 0.27 mmHg per 10 μm change in CCT for NCT (p < 0.0001) and IOP change of 0.19 mmHg per 10 μm change in CCT for GAT (p = 0.01). In this study of normotensive and POAG subjects, the Topcon CT-80 NCT showed an overestimation of IOP at the lower range and underestimation of IOP in normal and higher ranges of IOP. Clinicians should keep in mind that CCT influences IOP measurement with both types of tonometer and that the IOP readings obtained with these tonometers are not interchangeable.